faktor-faktor yang mempengaruhi pertumbuhan perusahaan - sumarna, alfonsa dian (Jurnal Benefita, 2016)
Result of the hypothesis testing showed that independen variable like firm-size is significant negative with company growth and  internal finance, external finance and growth opportunities is significant positive with company growth but independen variable like  firm-age didn’t have any significant with company growth. The result also showed that small company is growthing faster that then medium and large enterprises.